Widening the knowledge of non-employment as a risk factor for suicide: a Norwegian register-based population study - Carine Øien-Ødegaard; Lars Johan Hauge; Kim Stene-Larsen; Solveig Tobie Glestad Christiansen; Espen Bjertness; Anne Reneflot (BMC, 2023)
Abstract Background There is a known association between employment status and suicide risk. However, both reason for non-employment and the duration affects the relationship. These factors are investigated to a lesser extent. About one third of the Norwegian working age population are not currently employed. Due to the share size of this population even a small increase in suicide risk is of importance, and hence increased knowledge about this group is needed. Methods We used discrete time event history analysis to examine the relationship between suicide risk and non-employment due to either unemployment or health-problems, and the duration of these non-employment periods. We analyze data from the Norwegian population registry from 2004 to 2014, which includes all Norwegian residents in the ages 19-58 born between 1952 and 1989. In total the data consists of 1 063 052 men and 1 024 238 women, and 2 039 suicides. Results The suicide risk among the non-employed men and women is significantly higher than that of the employed. For the unemployed men, the suicide risk is significantly higher than the employed within the first 18 months. For the unemployed women we only find a significant association with suicide risk among those unemployed for six to twelve months. The suicide risk is especially increased among those with temporary health-related benefits. In the second year of health-related non-employment men have eightfold and women over twelvefold the OR for suicide, compared to the employed. Conclusion There is an association between non-employment and suicide risk. Compared to the employed both unemployed men and men and women with health-related non-employment have elevated suicide risk, and the duration of non-employment may be the driving force. Considering the large share of the working age population that are not employed, non-employment status should be considered in suicide risk assessment by health care professionals and welfare providers.